PENYEBARAN GURU SMAN SE-KOTAMADYA BANJARMASIN SEBAGAI DASAR PENETAPAN REKRUTMEN DAN PENEMPATAN GURU - Herita Warni; Ahmad Sofyan; Wahyu Wahyu; Dharmono Dharmono (Vidya Karya, 2016)
Abstract:  The imbalance of the distribution of study field-teachers in state senior high schools (SMAN) in the whole area of Banjarmasin city has became the background of this research. This research aimed at: (1) describing the real condition of distribution of study fields-teachers in state senior high schools in Banjarmasin city, (2) describing the analysis of the number of study field-teachers needed for each state senior high school in the whole area of Banjarmasin city, and (3) identifying the number of study field-teachers that needed and exceed the need for each state senior high school in the whole area of Banjarmasin city. This survey research used the technique of interview and documentation in collecting data. The collected data were presented in the forms of tables and graphics and descriptively analyzed. The research result showed that: (1) there are 552 study field-teachers that spread in 13 state senior high schools in the whole area of Banjarmasin city, (2) the number of study field-teachers needed in state senior high schools in the whole area of Banjarmasin city were 593 teachers, and (3) study fields that exceed in the number of teachers needed were in the fields of religion education, civics education, English language, biology, physics, and counseling training. While study fields that lack of the number of teachers were in the fields of Indonesian language, math, chemistry, economy/ accountancy, sociology, geography, history, art, information and communication technique, local content, and foreign/ethnic language. Keywords: distribution, teacher, and state senior high school (SMAN) Banjarmasin.     Abstrak:  Kondisi belum meratanya penyebaran guru mata pelajaran di SMAN se-Kotamadya Banjarmasin mendorong penulis untuk melakukan penelitian yang bertujuan untuk: (1) mendeskripsikan kondisi rill penyebaran guru mata pelajaran di SMAN se-kota Banjarmasin, (2) mendeskripsikan analisis kebutuhan guru mata pelajaran di SMAN se-kota Banjarmasin, (3) mengidentifikasi kebutuhan dan kelebihan guru per mata pelajaran di SMAN se-kota Banjarmasin. Jenis penelitian ini adalah penelitian survey, dengan menggunakan teknik pengumpulan data berupa wawancara dan dokumentasi. Data yang diperoleh disajikan dalam bentuk tabel dan grafik selanjutnya dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa: (1) jumlah guru mata pelajaran yang tersebar di 13 SMAN se-kota Banjarmasin adalah sebanyak 552 orang, (2) Jumlah guru mata pelajaran yang diperlukan di SMAN se-kota Banjarmasin berdasarkan analisis kebutuhan adalah sebanyak 593 orang, (3) Kelebihan jumlah guru SMAN se-kota Banjarmasin terjadi pada mata pelajaran Pendidikan Agama, Pendidikan Kewarganegaraan, Bahasa Inggris, Biologi, Fisika, dan Bimbingan Konseling, sedangkan yang masih kekurangan guru terjadi pada mata pelajaran Bahasa Indonesia, Matematika, Kimia, Ekonomi/Akuntansi, Sosiologi, Geografi, Sejarah, Kesenian, Teknik Informasi dan Komunikasi, Muatan Lokal, dan Bahasa Asing/Daerah. Kata Kunci: penyebaran, guru, dan SMAN Banjarmasin